Вплив способів основного обробітку ґрунту на динаміку запасів продуктивної вологи в посівах ячменю ярого в умовах Північного Степу України - Цилюрик, Олександр Іванович; Tsyliuryk, Oleksandr; Чорна, Валентина Іванівна; Chorna, Valentina; Десятник, Лідія Модестівна; Desyatnyk, Lydia; Горщар, Владислав Іванович; Horshchar, Vladuslav (Інститут зернових культур, 2020)
Доведено, що в умовах північного Степу України формується непромивний водний режим з ненаскрізним найменш насиченим класом вологості, перевага полицевої системи обробітку ґрунту в додатковій акумуляції вологи протягом осінньо-зимового періоду в північному Степу відмічається в роки з морозними і сніжними зимами, повільним і тривалим сніготаненням, а мілкого мульчувального плоскорізного розпушування – за недобору нормативної суми опадів впродовж грудня - лютого, від- сутності снігового покриву і підвищеної вітрової активності. Урожайність ячменю ярого значно залежить від резервів ґрунтової вологи. В північному Сте- пу висока продуктивність ячменю ярого, при умові одержання своєчасних і повних сходів, форму- ється за рахунок вологозапасів, нагромаджених у глибоких шарах ґрунту протягом осінньо-зимового періоду. Встановлено, що у північному Степу запровадження консервуючого обробітку ґрунту (чи- зельного), у разі вирощування ячменю ярого за диференційованої системи обробітку, посилює накопичення вологи (на 91,0–179,0 м3/га) в осінньо-зимовий період за рахунок рослинних решток, які затримують більше снігу, особливо у теплі малосніжні зими. З’ясовано, що запровадження мілкої мульчувальної системи обробітку ґрунту, незважаючи на зниження урожаю зерна ячменю ярого, зумовлює більш економне витрачання вологи на одиницю урожаю – в 1,1–1,2 раза. Виявлено, що у разі проведення щорічно полицевого та диференційованого обробітку ґрунту в середньому за роки досліджень одержували високий рівень урожайності, а мінімізація обробітку в більшості років призводила до його зниження на 0,22–0,55 т/га. Запровадження чизельного обробітку ґрунту в системі диференційованого найбільш ефективне у посушливі роки і навіть дає кращі результати, ніж оранка, оскільки накопичується більше продуктивної вологи за рахунок значної кількості післяжнивних решток попередника на поверхні поля. The yield of spring barley significantly depends on the reserves of soil moisture, which ensures the implementation of all important life processes, including seed germination and rooting of seedlings, transpiration, thermoregulation and supply of nutrients to the plant. The productivity of spring barley is directly proportional to its moisture content. With sufficient soil moisture, favorable conditions for the growth and development of field crops, and ultimately increases their yield. In the northern steppe, high productivity of spring barley, provided timely and full germination, is formed due to moisture reserves accumulated in the deep layers of the soil during the autumn-winter period of the year. The purpose of the study was to study the influence of the methods of basic tillage on the accumulation and dynamics of soil moisture in spring barley crops and the level of its yield. Experimental studies were performed during 2004–2015 in a stationary field experiment at the Institute of Grain Crops of the National Academy of Sciences of Ukraine. The presence of wavy nanorelief during chiselling, as well as plant remains on the ridges contributed to a significant reduction in wind speed in the aboveground layer. Snowfall was concentrated in the depressions and was reliably protected from blowing. Due to this, the height of the snow cover here, according to our data, was the highest and amounted to – 14.3 cm, and as a result faster thawing of the soil and better accumulation of water. At the same time, the intensity of wet accumulation during the autumn-winter period when treated with chisel tools outweighed the options of shelf plowing by an average of 17.9 mm, and disking – 9.2 mm. The increased assimilation of cold precipitation during chiselling can also be associated with strip loosening of the soil in the furrows, which is typical for chisel units. It is established that in the northern steppe the use of canning (chisel) with a differentiated tillage system for spring barley increases the accumulation of moisture by 91.0–179.0 m2/ha in the autumn-winter period due to plant residues that retain more snow, especially in warm snowless winters. It is proved that the use of a fine mulching system of tillage, despite the reduction of grain yield, con- tributes to a more economical consumption of moisture per unit of crop in 1.1–1.2 times when growing spring barley. It was found that the use of annual shelf and differentiated tillage on average over the years of re- search provides the maximum level of yield, and the minimization of tillage in most years led to its reduction by 0.22–0.55 t/ha. The use of chiseling in a differentiated tillage system is most effective in dry years and even outweighs plowing due to the greater accumulation of productive moisture due to the presence of a significant portion of post-harvest residues of the predecessor that retain moisture under the mulch.
Influence of methods of basic tillage on the dynamics of productive moisture reserves in spring barley crops in the conditions of the northern Steppe of Ukraine
Keywords: ячмінь ярий; Spring barley; обробіток ґрунту; tillage; вологість ґрунту; soil moisture; удобрення; fertilizers; дискування; disking; урожайність; yield